Repayment behaviour of development financial institution borrowers / Chong Fen Nee, Rosita Haji Suhaimi and Nurhani Aba Ibrahim - Chong, Feng Nee; Suhaimi, Rosita; Aba Ibrahim, Nurhani (UITM Sarawak,Kampus Samarahan, 2011)
This study investigates the repayment pattern of Development Financial Institutions borrowers in Sabah and Sarawak. Additionally, factors such as demographic profile, loan characteristics and borrower-lender distance are examined to determine their relationships with repayment performance. A total of two hundred and forty-two queationnaires were collected during the study period and used for the analysis. Findings showed that 43% of the respondents default their credit obligations while the remaining take between one to six months to settle their monthly arrears. When the cross-tabulation analysis was used to identify the common demographic characteristics of the defaulters, it was found that most of the defaults are male, attain a lower level of education, have a higher total number of dependents and self employed. An empirical analysis on the impact of the factors affecting repayment performance of Development Financial Institutions using logistic regression analysis suggested that Development Financial Institutions should manage the borrower-lender distance actively and impose a collateral requirement in order to mitigate default peoblems.